Optimization of the structure of insulating composite materials - Zeljko Kos; Valerii Vyrovoi; Volodymyr Sukhanov; Mykhailo Zavoloka; Aleksandr Gokhman; Iryna Grynyova (Tehnički Glasnik, 2019)
The article deals with the interdependent relationship between the properties of a structure and the properties of a material, which sets the task of reducing them, even they are indistinguishable, to a certain integrity. The object of research and analysis in the article is a building structure, which is seen as an open self-organized complex structural system. In the main part, the processes of the formation of structures are considered, as well as the classification of structural elements. The article concludes with structural changes related to the self-support and self-development of the network of active elements, which allow the manifestation of adaptation effects and the design-system to function during the normalized period. The importance of self-organization processes during the development and operation of construction systems allow us to attribute it to a self-organizing system. Thus, the building structure can be represented as an open and complex self-organizing system.